2014
DOI: 10.4062/biomolther.2014.115
|View full text |Cite
|
Sign up to set email alerts
|

Paraquat Induces Apoptosis through Cytochrome C Release and ERK Activation

Abstract: Paraquat has been suggested to induce apoptosis by generation of reactive oxygen species (ROS). However, little is known about the mechanism of paraquat-induced apoptosis. Here, we demonstrate that extracellular signal-regulated protein kinase (ERK) is required for paraquat-induced apoptosis in NIH3T3 cells. Paraquat treatment resulted in activation of ERK, and U0126, inhibitors of the MEK/ERK signaling pathway, prevented apoptosis. Moreover, paraquat-induced apoptosis was associated with cytochrome C release,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Exposure of E18 neuroblast cells to low concentrations of PQ resulted in early increases in PKB, ERK1/2, and JNK1/2 phosphorylation . Seo et al found that PQ treatment resulted in the activation of ERK1/2, p38, and JNK MAPKs, but only ERK MAPK was associated with PQ‐induced apoptosis in mouse embryo fibroblast cell . PQ activates p38 and JNK MAPK signaling pathways and promotes the release of proinflammatory cytokines that facilitate cell death .…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of E18 neuroblast cells to low concentrations of PQ resulted in early increases in PKB, ERK1/2, and JNK1/2 phosphorylation . Seo et al found that PQ treatment resulted in the activation of ERK1/2, p38, and JNK MAPKs, but only ERK MAPK was associated with PQ‐induced apoptosis in mouse embryo fibroblast cell . PQ activates p38 and JNK MAPK signaling pathways and promotes the release of proinflammatory cytokines that facilitate cell death .…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial outer membrane permeabilization (MOMP) and mitochondrial swelling are the prominent characteristics of mitochondrial morphology during apoptosis 29 . The apoptotic signal ultimately activates ERK1/2 and Bax to promote MOMP, resulting in the release of cytochrome c and Caspase 3 activation 29 , 30 . Western blot results indicated that SFN persistently activated ERK1/2, upregulated Bax and Caspase 3 in a dose-dependent and time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In the intrinsic pathway, the pro-apoptotic signaling cascade is proceeded by the release of mitochondrial cytochrome C. ERK 1/2 belong to the family of mitogen-activated protein kinases (MAPKs) which are involved in different cell processes and cell death ( 44 ). Phosphorylation and, thus, activation of ERK 1/2 by extracellular stimuli (such as DAMPs) results in the release of cytochrome C ( 45 ). Indeed, our data indicate that the exposure of HS to cardiomyocytes results in an increased expression of phosphorylation of ERK 1/2 and cytochrome C release (Figures 2 A,B).…”
Section: Discussionmentioning
confidence: 99%